2009
DOI: 10.1002/j.2158-1592.2009.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Disruptions in the Supply Network‐from Dormant to Action

Abstract: Managing risks in supply networks is a complex task; more so in those supply networks where the core competence lies in dealing with natural disasters, complex emergencies, and large‐scale attacks—namely those of humanitarian, and military organizations where the price of failure can be counted in terms of the loss of life rather than, simply, reduced profits. This conceptual article examines the capabilities of these supply networks to manage such disruptions, based on their resource configuration in a dorman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
175
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(177 citation statements)
references
References 31 publications
(38 reference statements)
2
175
0
Order By: Relevance
“…Kovács and Tatham (2009) demonstrated that both humanitarian and military supply chains in contrast to commercial supply chains have to plan to respond for what they view as inevitable events such as natural or complex disasters. In comparison, commercial supply chains find difficulty in dealing with disruption and plan to improve resilience to overcome disruptions as quickly as possible (Christopher and Peck, 2004).…”
Section: Current Supply Chain Theory: Comparison Of Commercial Militmentioning
confidence: 99%
See 4 more Smart Citations
“…Kovács and Tatham (2009) demonstrated that both humanitarian and military supply chains in contrast to commercial supply chains have to plan to respond for what they view as inevitable events such as natural or complex disasters. In comparison, commercial supply chains find difficulty in dealing with disruption and plan to improve resilience to overcome disruptions as quickly as possible (Christopher and Peck, 2004).…”
Section: Current Supply Chain Theory: Comparison Of Commercial Militmentioning
confidence: 99%
“…In comparison, commercial supply chains find difficulty in dealing with disruption and plan to improve resilience to overcome disruptions as quickly as possible (Christopher and Peck, 2004). Similarly, humanitarian organisations focus on delivering aid to people affected by disasters; whilst military organisations need to prepare for (and engage in) warfare or peacekeeping missions (Kovács and Tatham, 2009). Both cases require the speedy mobilisation of resources and capabilities from a preparation phase to a recovery state as a response to a disruption.…”
Section: Current Supply Chain Theory: Comparison Of Commercial Militmentioning
confidence: 99%
See 3 more Smart Citations